2021
DOI: 10.1017/s1368980021004481
|View full text |Cite
|
Sign up to set email alerts
|

Are interventions delivered by healthcare professionals effective for weight management? A systematic review of systematic reviews

Abstract: Objective: There are many systematic reviews of weight management interventions delivered by healthcare professionals (HCP), but it is not clear under what circumstances interventions are effective due to differences in review methodology. This review of systematic reviews synthesises the evidence about: (a) the effectiveness of HCP-delivered weight management interventions and (b) intervention and sample characteristics related to their effectiveness. Design: The review of reviews invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In this study, we demonstrated that ILSM significantly reduced T2D scores and obtained statistically significant benefits for FBG, BMI, and intention to eat lowindex glycemic food at an 18-month follow-up based on the intention-to-treat analysis. This is encouraging as previous studies reported that the benefit of lifestyle interventions for diabetes prevention was typically sustained at 6 to 12 months [7]. This exciting result may suggest that early behavior interventions are expected to touch off a series of reciprocally reinforcing recursions and interactions via goal setting and ongoing environmental support, eventually driving intervention influence over time.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In this study, we demonstrated that ILSM significantly reduced T2D scores and obtained statistically significant benefits for FBG, BMI, and intention to eat lowindex glycemic food at an 18-month follow-up based on the intention-to-treat analysis. This is encouraging as previous studies reported that the benefit of lifestyle interventions for diabetes prevention was typically sustained at 6 to 12 months [7]. This exciting result may suggest that early behavior interventions are expected to touch off a series of reciprocally reinforcing recursions and interactions via goal setting and ongoing environmental support, eventually driving intervention influence over time.…”
Section: Discussionsupporting
confidence: 55%
“…6 Department of Family and Community Medicine, University of California, San Francisco, CA 94118, USA. 7 School of Nursing, University of California, San Francisco, CA 94118, USA. 8 School of Nursing, Yale University, New Haven, CT 06520, USA.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the role of a credible source, such as oncology counselor, has been highlighted in providing evidence-based information on the association of breast cancer and diet and physical activity in daily life in developing interventions effectively [ 68 ], and additionally in identifying the most important determinants of lifestyle changes in cancer survivors [ 69 ]. Moreover, it has been suggested that weight management interventions delivered by healthcare professionals can be effective for weight loss for up to 6 months [ 70 ]. The current findings concerning BCTs are in agreement with the aforementioned outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, by Phase 2, issues of understanding were more prominent, which was related to the messaging changing frequently and mitigations being implemented, removed and re-implemented. Guidance from behavioural scientists should be followed to promote understanding and compliance with public health messages [ 42 ], and also to better understand the social psychology of visible behavioural mitigations such as wearing face coverings [ 38 ]. Reliance on behavioural mitigations is complex.…”
Section: Discussion/recommendationsmentioning
confidence: 99%